Growth and yield comparison of rice plants treated with encapsulated Trichoderma asperellum (UPM40) in response to drought stress - Yusup, Iffatul Arifah; Mohammad Yusoff, Martini; Ismail, Mohd Razi; Berahim, Zulkarami; Adzmi, Fariz (Universiti Putra Malaysia Press, 2023)
During low rainfall periods, rice plants often face drought stress, which would significantly affect rice yield. One of the methods to mitigate the problem is incorporating rice plants with fungi such as Trichoderma. This study evaluated the effects of encapsulated Trichoderma asperellum (UPM 40) on the growth and yield of rice plants planted in saturated and flooded soil conditions in response to drought stress. A randomized complete block factorial design was implemented with four replications and two factors. The first factor was encapsulated T. asperellum (UPM 40) concentration of 0 and 5 g. The second factor was the soil condition: saturated and flooded soil. The drought stress was imposed by halting watering during early anthesis for 14 days and resumed afterward. One of the significant interaction effects detected was on the relative water content of rice plants planted in flooded soil conditions and treated with T. asperellum (UPM 40), where the value was 78.51%, higher than the control of 72.09%, which showed the ability of the fungus to help rice plants alleviate detrimental effects of drought stress and delay the onset of adverse effects of drought stress. Thus, it contributed to the crop’s simultaneous improvement in rice yield compared to untreated plants in saturated soil. Applying 5 g encapsulated T. asperellum (UPM 40) to the rice plants would perform best in flooded soil conditions during drought stress.